Female genital cutting in Malaysia: a mixed-methods study - Abdul Rashid; Yufu Iguchi (BMJ Open)
Objective This study aimed to understand the reasons for the practice by the Muslim community, traditional practitioners and the views of religious scholars as well as the medicalisation trend of the practice of female genital cutting (FGC).Design This is a mixed-method (qualitative and quantitative) study. A questionnaire was created and used by three trained research assistants for the quantitative component of the study. The qualitative component of the study included in-depth interviews and focus group interviews.Setting This study was conducted in rural areas of two states in the Northern Peninsular Malaysia.Participants Due to the sensitive nature of the study, the study sample was chosen using a snowball sampling method. Two of the three Northern states Mufti’s approached consented to participate in the study.Results Quantitative: There were 605 participants, most had undergone FGC (99.3%), were in the opinion FGC is compulsory in Islam (87.6%) and wanted FGC to continue (99.3%). Older respondents had FGC conducted by traditional midwives (X2=59.13, p<0.001) and younger age groups preferred medical doctors (X2=32.96, p<0.001) and would permit doctors (X2=29.17, p<0.001) to conduct FGC on their children. These findings suggest a medicalisation trend. Regression analysis showed the odds of FGC conducted by traditional midwives and nurses and trained midwives compared with medical doctors was 1.07 (1.05; 1.09) and 1.04 (1.01; 1.06), respectively. For every 1-year decrease in age, the odds of participants deciding medical doctors should perform FGC as compared with traditional midwives increase by 1.61.Qualitative: Focus group discussions showed most believed that FGC is compulsory in Islam but most traditional practitioners and the Mufti’s stated that FGC is not compulsory in Islam.Conclusion Almost everyone in the community believed FGC is compulsory in Islam and wanted the practice to continue, whereas the traditional practitioners and more importantly the Mufti’s, who are responsible in issuing religious edicts, say it is not a religious requirement.